Assessing Pharmacists' Views and Barriers to Providing and Billing for Pharmacist-Provided Health Care Services. (August 2021) - Biddle, Michael A.; Cleveland, Kailyn K.; O'Connor, Shanna K.; Hruza, Hayli; Foster, Madeline; Nguyen, Elaine; Robinson, Renee; Wadsworth, Thomas
Background: The role of Idaho and Alaska pharmacists in providing health care services has steadily broadened over recent years. With many new pharmacist-provided health care service possibilities, this study assessed the impact of these advancements on community pharmacies.Objective: The objective of this study was to identify current pharmacist-provided health care services and pharmacist-perceived barriers to providing and billing for these services in Idaho and Alaska community pharmacies.Methods: A questionnaire was developed focusing on 2 areas: providing services and billing for services. Pharmacy students on experiential rotations administered the questionnaires to pharmacists at their rotation sites. Pharmacists at community pharmacy practice sites in Idaho and Alaska completed the questionnaire in an interview format conducted by students. Likert-type scale data were analyzed using descriptive statistics. Because the study did not include a comparator group, no power calculation was conducted. All open-response answers were analyzed independently by 2 researchers and discrepancies in coding open-ended questions were resolved by discussion with a group of 4 researchers.Results: Most pharmacists reported that they already provide non-dispensing services, desired to implement new services, and had confidence in their team's ability to handle new services. Time and resources were the most cited barriers to providing new services; compensation, company support, and education were the most cited barriers to billing for services.Conclusions: Community pharmacists already provide non-dispensing services and many are looking to provide more services, but barriers of time, resources, compensation, company support, and education will need to be overcome to move forward.